CURRENT-BASED HYBRID MOMENT METHOD ANALYSIS OF ELECTROMAGNETIC RADIATION AND SCATTERING PROBLEMS - Jakobus, Ulrich (Applied Computational Electromagnetics Society Journal (ACES), 2022)
A current-based hybrid method combining the method of moments (MM) with asymptotic current expansions for the higher frequency range is presented for the analysis of arbitrarily shaped, three-dimensional, perfectly conducting electromagnetic radiation and scattering problems. Some examples demonstrate the drastic saving in memory requirement and CPU-time when applying the hybrid method as compared to the conventional MM. Even though the proposed method is a frequency domain formulation, some time domain results based on a Fourier transform are presented as they show an accurate description of diffracted and creeping waves. [Vol. 10, No. 3 (1995), Special Issue on Advances in the Application of Method of Moments to Electromagnetic Radiation and Scattering Problems, pp 38-46